Change management Strategy of Digital Television Broadcasting (DTV) Implementation in TVRI Stasiun Jawa barat using Adkar Model and Positive Psychological Capital - Fawzy, Reza Marta; Bangun, Yuni Ros (Journal of Business and Management, 2014)
According to the regulation of Ministry of Communication and Informatics Republic of Indonesia Number 32 Year 2013 about the Implementation of Digital Television Broadcasting and Multiplexing Broadcasting through Terrestrial System, all of broadcasting institutions particularly TVRI has to pioneer the implementation of digital television broadcasting (DTV) from analogue TV in Indonesia which must be completed in 2018. The transformation is aimed to create better quality TV in Indonesia which also can encourage new business opportunities. The implementation of DTV is run gradually. The implementation generates change management especially related to budget aspects and human resources. In this research, the data collection was accomplished by distributing questionnaires for 75 employees in TVRI Stasiun Jawa Barat and interviewing Board of Directors and Chief of Information and Technology of TVRI Stasiun Jawa Barat during June until August 2014. This research has purpose to formulate the strategy of change management in TVRI Stasiun Jawa Barat. In compiling change management strategy, researcher will use ADKAR model to approach the process of change plan. Researcher also use Positive Psychological Capital to measure the characteristics of human resources needed for achieving DTV program. In the final of the research, the researcher proposed several recommendations such as strategic communication implementation and strategy of encouraging employees’ skills to support DTV program in accordance the change management in TVRI Stasiun Jawa Barat can be done effectively. Keywords: Change Management, ADKAR Model, Positive Psychological Capital, Digital Television Broadcasting